(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Within the rapidly growth of internet, web-based applications are getting additional interest to investigate new and efficient methods to design and develop such applications. The Web Site Design Method (WSDM) is a followed process to develop web applications but it has the drawback of not including a testing phase within its lifecycle process. In this paper we are proposing an integrated model for WSDM with Rapid Application Development (RAD) model.